2015
DOI: 10.5603/ep.2014.0065
|View full text |Cite
|
Sign up to set email alerts
|

Ekspresja receptorów folitropiny w gruczolakach przysadki — marker agresywności guza?

Abstract: Introduction: In our earlier study, we found that pituitary adenomas, like other human tumours, express ectopically follicle stimulating hormone receptors (FSHR) in intratumoural blood vessels endothelia and/or tumoural cells. The aim of the present paper was to provide more detailed data on FSHR expression in different subtypes of pituitary adenomas and to evaluate its possible role as a prognostic and/ or predictive biomarker in these tumours. Material and methods: Forty two pituitary adenomas, surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(17 reference statements)
1
7
0
Order By: Relevance
“…Study found that FSHR in tumor cells was overexpressed in aggressive PAs compared to non-aggressive PAs [26]. In this study, Western blot analysis revealed that FSHR was significantly upregulated in FSH-positive relative to negative NFPAs ( p < 0.05) (Fig.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…Study found that FSHR in tumor cells was overexpressed in aggressive PAs compared to non-aggressive PAs [26]. In this study, Western blot analysis revealed that FSHR was significantly upregulated in FSH-positive relative to negative NFPAs ( p < 0.05) (Fig.…”
Section: Resultssupporting
confidence: 49%
“…It is necessary to stratify such type of PA patients, reveal their invasive and aggressive mechanisms, and discover the effective biomarkers so as to provide an effective prediction, prognosis, targeted therapy, and personalized treatment strategy. It was reported that FSHR expression in PAs was a marker of aggressiveness [26], and FSHR must bind with FSH to exert their biological roles. Moreover, FSH-positive expressed NFPAs were one of NFPA subtypes [20, 33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells of the vessels present in normal-appearing tissues at a distance >10 mm outside the tumors or normal prostate were FSHR-negative (26). In subsequent studies, endothelial FSHR expression was shown in thyroid and neuroendocrine tumors (35, 37, 40). Several groups suggested that the FSHR observed in TVECs and cancer cells is functional (2426, 7072).…”
Section: Fshr In Cancer and Tumor Vessel Endothelial Cells (Tvecs)mentioning
confidence: 93%
“…In pituitary adenomas FSHR expression in tumoral cells is prevalent in invasive and proliferating tumours [22]. Thus, the immunostaining of FSHR could play a supplementary role in the histopathological examination.…”
Section: Fshr Expression: a Marker Of Malignancy?mentioning
confidence: 99%